Distinct Treatment Outcomes of Antiparasitic Therapy in Trypanosoma cruzi-Infected Children Is Associated With Early Changes in Cytokines, Chemokines, and T-Cell Phenotypes - Albareda, María C.; Natale, María A.; De Rissio, Ana M.; Fernandez, Marisa; Serjan, Alicia; Alvarez, María G.; Cooley, Gretchen; Shen, Huifeng; Viotti, Rodolfo; Bua, Jacqueline; Castro Eiro, Melisa D.; Nuñez, Myriam; et al. (Frontiers in Immunology, 2018)
Background. In contrast to adults, Trypanosoma cruzi-infected children have more broadly functional Trypanosoma cruzi-specific T cells, and the total T-cell compartment exhibits fewer signs of immune exhaustion. However, not much is known about the link between immunocompetence and the treatment efficacy for human Chagas disease. Methods. Using cytokine enzyme-linked immunosorbent spot (ELISPOT) polychromatic flow cytometry, cytometric bead assay, multiplex serological assays and quantitative PCR, we evaluated T. cruzi-specific T-cell and antibody immune responses, T-cell phenotypes and parasitemia in children in the early chronic phase of Chagas disease undergoing anti-Trypanosoma cruzi treatment. Results. Treatment with benznidazole or nifurtimox induced a decline in T. cruzi-specific IFN-γ- and IL-2-producing cells and proinflammatory cytokines and chemokines. T-cell responses became detectable after therapy in children bearing T-cell responses under background levels prior to treatment. The total frequencies of effector, activated and antigen-experienced T cells also decreased following anti-T. cruzi therapy, along with an increase in T cells expressing the receptor of the homeostatic cytokine IL-7. Posttreatment changes in several of these markers distinguished children with a declining serologic response suggestive of successful treatment from those with sustained serological responses in a five-year follow-up study. A multivariate analysis demonstrated that lower frequency of CD4+CD45RA—CCR7—CD62L— T cells prior to drug therapy was an independent indicator of successful treatment. Conclusions. These findings further validate the usefulness of alternative metrics to monitor treatment outcomes. Distinct qualitative and quantitative characteristics of T cells prior to drug therapy may be linked to treatment efficacy.